Meningkatkan Hasil Belajar Servis Bawah Bola Voli Mini Menggunakan Metode Pembelajaran Bagian Pada Siswa Kelas V di SD Negeri 218/VIII Cermin Alam Kecamatan VII Koto Ilir Kabupaten Tebo - ENDRI JASMAN; Ermi Ermi (Jurnal Muara Olahraga, 2018)
One material for Physical Education for Elementary School students is a volleyball game. One form of volleyball game taught to elementary school students is a mini volleyball game. In volleyball learning, various basic techniques are taught. One of the most important techniques is service technique. Based on the type, volleyball services are divided into two types, namely bottom service and top service. This study aims to determine whether there is an increase in the results of learning services under mini volleyball using part learning methods in fifth grade students of SD Negeri 218 / VIII Cermin Alam District VII Koto Ilir, Tebo Regency. The bottom service material is carried out in class V with 27 students, consisting of 15 male students and 12 female students. The final result of student understanding (cognitive) with an achievement of 88.89% which entered the criteria very well. The final result of observing student behavior (affective) with an achievement of 100% that falls into very good criteria. The final result of observing student (psychomotor) skills with an achievement of 96.29% which falls into good criteria.